Determinantes de una elección errada al escoger medicamentos de venta libre (2010)
This study evaluates the probability of confusion among consumers regarding six categories of over-the-counter medications. The estimates are based on an experimental design in which time and the presence of brands are the variables addressed. Additionally, it is controlled using recollection and consumption habits regarding brands. Using three types of analysis (contingency table, tree regression and logic regression), the results show that recollection and the presence of brands are the two variables that reduce the probability of confusion. The results are not applicable to other categories; however, recollection and the presence of brands do turn out to be significant variables when evaluating the probability of consumer confusion.